Are trade and transport logistics activities mutually reinforcing? Some empirical evidences from ASEAN countries - Kee-hung Lai; Yu Pang; Christina W. Y. Wong; Y. H. Venus Lun; Y. N. Eppie Ng (Journal of Shipping and Trade, 2019)
Abstract Both trade and transport logistics activities have impressively flourished among the Association of Southeast Asian Nations (ASEAN) countries over the past decades. Based on these observations, this paper conjectures that trade liberalization and transport logistics development are mutually reinforced. Elimination of internal tariff in the free trade area facilitates trade thereby increasing the demand for transport logistics. Transport logistics development generates spillover effect to promote trade with nonmembers. The findings of this paper indicate that a country’s transport logistics development will bolster both of its regional and global trade development.